2017
DOI: 10.1097/tp.0000000000001320
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid Use and Growth After Pediatric Solid Organ Transplantation

Abstract: Corticosteroid withdrawal/avoidance in pediatric renal transplantation is associated with a significant improvement in height. Prepubertal patients appeared to have the greatest benefit. Importantly, the improvement in growth was not accompanied by increased rejection or worsening patient/allograft survival in the short term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 35 publications
3
28
0
Order By: Relevance
“…Estimated GFR (eGFR, updated Schwartz formula) based on centrally recorded observed values. Box plots represent median and interquartile range; means are connected by lines; whiskers extend to the 10th and 90th percentile; dots represent outliers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Estimated GFR (eGFR, updated Schwartz formula) based on centrally recorded observed values. Box plots represent median and interquartile range; means are connected by lines; whiskers extend to the 10th and 90th percentile; dots represent outliers.…”
Section: Resultsmentioning
confidence: 99%
“…Children are exposed to immunosuppression for longer, increasing their risk for malignancies, viral infections, and CNI‐related renal and metabolic complications such as diabetes. In addition, “standard” immunosuppressive protocols with long‐term corticosteroid use impairs longitudinal growth and contributes to metabolic derangements that have cardiovascular consequences …”
Section: Introductionmentioning
confidence: 99%
“…Because each center has a small number of recipients in each of those increased risk subgroups, single‐center studies provide limited information. Analyses, to date, suggest that in those higher‐risk subgroups, RDP did not decrease patient or graft survival rates .…”
Section: Discussionmentioning
confidence: 89%
“… reported that RDP was not associated with an increased risk of graft loss to disease recurrence. Additionally, two recent multicenter prospective randomized studies, as well as two recent reviews and meta‐analyses—all involving pediatric recipients—found no difference in patient and graft survival rates in RDP versus maintenance prednisone recipients .…”
Section: Discussionmentioning
confidence: 98%
“…25 less favored because of their effects on growth. 26,27 Avoiding corticosteroids after transplantation can significantly increase a child's height without adversely affecting rejection, graft loss, or patient survival rates. 28 Our patient who had a history of cytomegalovirus infection prior to transplantation was treated with oral valganciclovir, and the subsequent reactivation was assumed to have been caused by excessive immunosuppression from the corticosteroids (Figure 1).…”
Section: Patient Outcomesmentioning
confidence: 99%